A Brief Clinical Study: The Use of a Custom Guide for Scapula Free Flap Harvest and Mandibular Reconstruction. Issue 7 (26th October 2022) - Chundoo, Shima; Naredla, Prady; Thomas, Suraj
Abstract : Head and neck cancer can leave patients with significant defects requiring major reconstruction. The scapula free flap remains a relatively underused flap choice. This article examines the novel use of a custom guide for a scapula free flap in mandibular reconstruction following resection. A case file was created involving a consultant surgeon, KLS advisor, and technical team based in Belgium. A computed tomography scan of the mandible was sent electronically to render a 3-dimensional model. Custom cutting guides for resection and scapula graft harvest were fabricated. A custom plate for fixation was also developed. The scapula free flap was successfully placed using custom guides. In this case, the use of a custom guide enabled easier harvest, manipulation, and handling of the scapula free flap into the defect. The use of new technology and computer-generated guides represents a considerable shift forward into improving precision in complex surgical procedures and reducing intraoperative time. The use of a custom guide can provide an easier means to handle and manipulate one of the largest free flaps in surgery, the scapula free flap.